A comparative analysis of profitability of non-banking financial institutions in Bangladesh and investors’ investment decision making - Sanah, Shaika Samreen (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.